Multiple Dissipative Devices for Blast-Resisting Cable-Supported Glazing Façades. (3rd November 2013) - Amadio, Claudio; Bedon, Chiara
Abstract : The paper analyzes the structural response of a high-level air blast loaded cable-supported façade. Since the glass panels and the cables present a typical brittle behavior and are subjected to elevated tensile stresses when a high-level explosion occurs, multiple dissipative devices are simultaneously introduced in the conventional glazing system to mitigate the maximum effects of the design blast wave. Dynamic analyses are performed using a sophisticated FE-model to describe accurately the response of the façade equipped by dissipative devices. Based on numerical results of previous contributions, viscoelastic spider connectors (VESCs) are introduced in the points of connection between glass panels and pretensioned cables, to replace "rigid" spider connectors commonly used in practice. At the same time, rigid-plastic frictional devices (RPDs) are installed at the top of the bearing cables to mitigate furthermore the bracing system. As a result, due to the combined use of VESCs and RPDs opportunely calibrated, the maximum tensile stresses in the glass panels and in the cables appear strongly reduced. In addition, the proposed devices do not trouble the aesthetics of such transparent structural systems. At last, simple design rules are presented to predict the response of cable-supported façades subjected to high-level dynamic loads and to preliminary estimate the mechanical parameters of combined VESCs and RPDs.